From the Putumayo to Connemara: Roger Casement’s Amazon Voyage of Discovery - Harris, Peter James (ABEI Journal, 2002)
This article examines the evidence provided by Roger Casement’s accounts of his voyage to the Putumayo in the Amazon rain forest in 1910, in order to reveal the Odyssean complexity of his personality and to suggest that, in a metaphorical sense at least, this journey represented the beginnings of an Irish homecoming for Casement, just as the wanderings of Homer’s hero led him to the recovery of his house and kingdom in Ithaca.